Determinants of scabies severity among students in Islamic boarding schools in Indonesia: a cross-sectional study - Munir, Miftahul; Rahmawati, Naili; Sani, Mohd Hijaz Mohd (Jurnal Ners, 2026)
Introduction: This study aimed to identify the determinants associated with increased scabies severity among students in pesantren in Indonesia. Methods: A cross-sectional study was conducted to identify the determinants of increasing scabies severity among clinically confirmed cases in Islamic boarding schools, involving 120 students from six schools in Lamongan and Tuban. Data were collected using a modified and validated questionnaire, and nutritional status was assessed using body mass index (BMI). All participants were clinically diagnosed with scabies. Severity was categorized as mild, moderate, or severe based on the number of lesions and clinical manifestations. All instruments underwent content validity and reliability testing (Cronbach’s alpha ≥ 0.70), and ordinal logistic regression (proportional odds model) was applied to identify predictors of increasing scabies severity (p < 0.05) using SPSS version 25. Results: Frequent sharing of personal items was the strongest predictor of greater severity. Students who sometimes shared items had odds ratio (OR) of 3.01 (95% confidence interval [CI]: 1.45–6.60; p = 0.003), while frequent sharing increased the odds to 9.06-fold (95% CI: 3.00–27.40; p < 0.001). Good personal hygiene markedly reduced severity (OR = 0.04; 95% CI: 0.01–0.25; p = 0.002). Adequate residential density and longer duration of stay were also protective factors. Nutritional status and general knowledge were not consistently associated with severity. Conclusions: Scabies severity in pesantren is primarily driven by modifiable behavioral and environmental factors. Reducing shared-use practices and strengthening hygiene interventions may substantially mitigate disease severity in communal boarding school settings.